CAMINHO GEOLÓGICO-GEOMORFOLÓGICO NA UNIVERSIDADE FEDERAL DO ESPÍRITO SANTO (CAMPUS DE GOIABEIRAS) - VITÓRIA (ES) - Dias, Jane (2019)
The general objective of this research is to propose geological-geomorphological paths at the Espírito Santo Federal University (Goiabeiras Campus), using concepts of geotourism, in order to suggest the geoconservation of these areas of geological and geo